Acute abdomen caused by rupture of a torted intra-abdominal testicular mass: Case report. (2020) - Ghobashy, Ahmed; Hasan, Doaa; AbdElsalam, Ahmed; Ahmed, Aboubakr; Arafat, Ahmed; Tarek, Mahmoud; Ragab, Moutaz
Highlights: Scrotal examination is an integral part of the abdominal examination. Intra-abdominal location of undescended testis accounts for about 10 % of the cases. Intra-abdominal location harbors a higher risk for malignancy. Torsion of the cryptorchid testis is a very rare cause of acute abdominal pain. Abstract: Introduction: Cryptorchidism is defined as the absence of one or both testicles from the scrotum, which is considered one of the most common birth defects of male genitalia. Mostly the undescended testes are in the inguinal region, while the intra-abdominal location accounts for only 10 % of the cases. The potential risk of malignant transformation in an undescended testis is approximately 2.5–8 times higher than in scrotal position. Torsion of the cryptorchid testis is a very rare cause of acute abdominal pain with few cases published in literature. Case presentation: A 44-year-old male patient presented to the emergency room with acute abdominal pain. General examination revealed relevant tachycardia. Upon abdominal examination there was tenderness and rebound tenderness all over the abdomen, more evident in the lower abdomen. Interestingly, routine examination of the inguino-scrotal region revealed empty right hemi-scrotum despite the patient not being aware. Routine blood tests showed marked anemia Hb: 7.4 g/dl. Urgent pelvi-abdominal U/S showed moderate free intra-abdominal collection in addition to a pelvic mass. CT of the abdomen showed a well-defined heterogenous hypodense mass measuring about 8.5 × 5.5 cm in the pelvis. Urgent exploratory laparotomy was done, and a mass was found to be torted and ruptured. Excision was done and histo-pathological examination revealed testicular mixed germ cell tumor. Conclusion: Undescended testis is associated with an increased risk of infertility, testicular cancer and torsion. In any male with undescended testis and intra-abdominal mass; the risk of intra-abdominal testicular tumor should be considered.